Apoptotic Induction in Human Colorectal Adenocarcinoma Cell Line and Growth Inhibition of Some Gastrointestinal Pathogenic Species by Lactobacillus Sakei Metabolites - Mohammad Saber Malaki; Leila Rouhi; Khalil Khashei Varnamkhasti (Tehran University of Medical Sciences, 2021)
Background and Aim: Lactobacillus is the most important genus of lactic acid bacteria and the use of some species of lactobacillus with the probiotic potential can be effective for inhibition of the growth of some pathogens and control of  gastrointestinal diseases and cancers. In this study, the pro-apoptotic and antimicrobial effect of Lactobacillus sakei on human colorectal adenocarcinoma cell line and some gastrointestinal pathogenic species was examined.  Materials and Methods: In this study, the antimicrobial activity of metabolites of Lactobacillus sakei was assessed by Well Diffusion Agar (WDA) method against some gastrointestinal pathogenic bacteria. HT-29 colorectal adenocarcinoma cancer cells were cultured in DMEM medium with 10% bovine serum. The cells were treated in 5, 10, 15 and 20 mg/ml concentrations of sakei metabolites and incubated at 24 and 48 hours. Apoptosis was analyzed by Annexin V-FITC/PI kit according to the manufacturers protocol in both incubation times. For error reduction, each test was performed in triplicate Results: The results of this study indicate that sakei  was able to produce antimicrobial metabolites against gastrointestinal pathogenic bacteria. Also, the results of the Annexin test showed that with increasing concentration of sakei metabolites in dose dependent manner, induction of apoptosis in this cell line increases (P<0.05). Conclusion: It seems that there is a good research field for the use of bioactive compounds produced by Lactobacillus sakei in the control of gastrointestinal pathogenic bacteria and treatment of human colorectal adenocarcinoma.